Utilization of Shell Waste as Fine Aggregate in K225 Quality Concrete - Utomo, Satriyo; Rahmasari, Puspita; Supardi, Iwan; Riyanti, Eva; Robert (International Journal of Research in Vocational Studies (IJRVOCAS), 2026)
Conventional concrete materials derived from natural resources cause environmental problems. This encourages the development of concrete using recycled materials for sustainability reasons. One such material is shellfish, which is used to replace aggregates in concrete, both fine and coarse aggregates. This study conducted an experimental study using shellfish waste as a fine aggregate in a concrete mixture. Utilization of shellfish waste not only reduces environmental problems but can also provide economic value to construction, as well as an effort to conserve natural resources. Shellfish waste was obtained from the coast of Mempawah Regency. The planned test specimens were 15x15x15 cm cubes with a target quality of K225 kg/cm². The test specimens were made with a composition of sand with shellfish sand in proportions of 0%, 5%, 7%, 9%, and 100%. Physical properties of shellfish sand were tested, slump tests were conducted to determine the effect of shellfish sand on concrete viscosity, and concrete compression tests were conducted at the age of 28 days to determine the effect of shellfish sand on concrete strength. The compressive strength test results with 0% substitution = 246.22 kg/cm² or 24.15 MPa. 5% substitution = 211.98 kg/cm² or 20.79 MPa, resulting in a 5.79% decrease in quality. 7% substitution = 195.10 kg/cm² or 19.3 MPa, resulting in a 13.29% decrease in quality. 9% substitution = 176.14 kg/cm² or 17.27 MPa, resulting in a 21.72% decrease in quality. 100% substitution = 155.56 kg/cm² or 15.25 MPa, resulting in a 30.86% decrease in quality. The greater the substitution of the shell sand mixture, the greater the decrease in quality.